THE MAIN ASPECTS OF CONTINENTAL POLICY OF GREAT BRITAIN IN THE EUROPEAN UNION (International relations and international law Journal, 2016)
The article is devoted the main aspects of continental policy of the Great Britain in European Union. The author analyzing the role of Great Britain in European integration.
Keywords: continental policy; Great Britain